Analysis and Study of Embankment Subsidence in Reclamation Works on Soft Soil - Cindy Aq'tavia; Helmy Darjanto (LPPM NAROTAMA UNIVERSITY, Indonesia, 2022)
The rapid development of transportation facilities and the increasing population along the coastline, tends to utilize coastal land as a human activity, one of which is by conducting coastal reclamation. Where in the coastal areas of Indonesia are often found soft soil. The problem with soft soil is low bearing capacity and stability. It is necessary to improve the soil on soft cohesive soils. One of them is by installing a Vertical Drain to speed up consolidation time. In this research study, a vertical drain with a triangular pattern of 1m distance with 4m embankment decreased by 0.04m/year and accelerated consolidation time from 2.57 years to 42 weeks and with the help of the Plaxis 8.6 program got a safety value of 1,409.